Fundamentals of epidemiology - Christiansen-Lindquist, Lauren; Wall, Kristin M. (Springer Publishing Company, LLC, 2024)
"We believe now more than ever that the fundamentals of epidemiology provide an essential critical thinking framework to help navigate the constant flow of health (mis)information. While we would be thrilled if all our readers joined the epidemiologic workforce, we have written this text with the goal of being accessible to future epidemiologists as well as those who will pursue careers in anything from the arts to zoology"--